Ventilação natural em edificações residenciais: parâmetros normativos para configuração das aberturas - Passos, Isabela Cristina da Silva (2017)
Natural ventilation is one of the main phenomena that affect thermal comfort in tropical climate regions. Its use as a bioclimatic strategy can mean energy saving with air conditioning systems. However, the normative recommendations in Brazil are incomplete and divergent, in relation to natural ventilation in buildings use. The majority of them refers only to the entrance opening area, relating it to the floor area, showing the lack of a standard that consider, in an integrated way, openings dimension and others important aspects that affect natural ventilation in buildings. The present work sought to identify parameters of openings configuration that can be incorporated into the Brazilian Standards for a better orientation to the designers. Parametric analyzes were performed with Computational Fluid Dynamics (CFD) modeling through the PHOENICS VR 3.6.1 program. A representative model of a multifamily residential building was chosen which allowed the simulation of several variables that influence natural ventilation performance. This model was adapted with different configurations of openings by varying the size of inlet and outlet openings, the porosity of internal doors and the orientation in relation to external winds. The modifications made resulted in a total of 26 simulated models which in each of them were considered open all rooms of ground floor and third floor. Initially, the models were simulated with external air velocity of 2m/s, which was the average between Brazilian capitals, as well as the most frequent average value. After that, the best and the worst cases were simulated using the external air velocity of 3m/s, in order to compare them. The results were divided into qualitative and quantitative data. In general, the models with greater opening area and greater door porosity obtained greater results of internal air speed, being that the models with the wind incident to 135 ° had a more uniform distribution between the apartments. The model with the highest frequency of internal velocities above 0,4 m/s was the model with 25% opening area in relation to the floor area, 100% porosity of the internal doors and 48% of outlet opening area in relation to the inlet opening area in the apartment. The results showed the strong influence of openings design, internal doors porosity and orientation in the natural ventilation performance, leading to believe that only the size of the entrance openings is not sufficient to provide a satisfactory natural ventilation performance in residential buildings. Recommendations for windows configuration in residential building in Brazil were elaborated according to the Bioclimatic Zoning. It is suggested that the normative recommendations be reviewed considering the recommendations made in this thesis.